Digi teacher as a teaching aid / Mohd Zainy Mohd Jalal and Mohd Radzuan Othman - Mohd Jalal, Mohd Zainy; Othman, Mohd Radzuan (1999)
‘Digi Teacher’s, as teaching aid is very useful as a teaching aid for a student of digital electronics. In digital system, the popular gates are used liked AND gates, OR gates, EX- OR gates, Inverter gates, NAND gates, NOR gates, EX-NOR gates and buffer. In Digi teacher application focuses on the outputs that neither can be obtained from certain inputs, after being through NOR gates and INVERTER (ICs). The studies of the IC’s such as 7402 quadruple 2- input NOR-Gates, 7404 Hex INVERTER and LED was made and evaluated. This unit can be improved by using rotary switch and three 7402 quad 2- input NAND-gates IC’s for better and easy handling for beginners. In Digi Teacher, the user no need to memorized al the basic truth table for all the logic gates. In this case, Digi Teacher was developed for improved the general truth table where it’s as a teaching aid, which can test all the gates in the digital electronic.